On Distance-Based Topological Descriptors of Chemical Interconnection Networks - Min Hu; Haidar Ali; Muhammad Ahsan Binyamin; Bilal Ali; Jia-Bao Liu; Chengmei Fan (Journal of Mathematics)
Structure-based topological descriptors of chemical networks enable us the prediction of physico-chemical properties and the bioactivities of compounds through QSAR/QSPR methods. Topological indices are the numerical values to represent a graph which characterises the graph. One of the latest distance-based topological index is the Mostar index. In this paper, we study the Mostar index, Szeged index, PI index, ABCGG index, and NGG index, for chain oxide network COXn, chain silicate network CSn, ortho chain Sn, and para chain Qn, for the first time. Moreover, analytically closed formulae for these structures are determined.